Sleep Deprivation Induces Cognitive Impairment by Increasing Blood-Brain Barrier Permeability via CD44 - Sun, Jing; Wu, Jusheng; Hua, Fuzhou; Chen, Yong; Zhan, Fenfang; Xu, Guohai (Frontiers in Neurology, 2020)
Sleep deprivation occurs frequently in older adults, which can result in delirium and cognitive impairment. CD44 is a key molecular in blood-brain barrier (BBB) regulation. However, whether CD44 participates in the roles of sleep deprivation in cognitive impairment remains unclear. In this study, the effect of sleep deprivation on cognitive ability, tissue inflammation, BBB permeability, and astrocyte activity were evaluated in vivo. The differentially expressed genes (DEGs) were identified by RNA sequencing. The overexpression of CD44 and BBB model in vitro was performed to assess the effect and mechanisms of CD44. Sleep deprivation impaired the learning and memory ability and increased the levels of inflammatory cytokines, along with increased BBB permeability and activated astrocytes in hippocampus tissue. RNA sequencing of hippocampus tissue revealed that 329 genes were up-regulated in sleep deprivation induced mice compared to control mice, and 147 genes were down-regulated. GO and pathways showed that DEGs were mainly involved in BBB permeability and astrocyte activation, including nervous system development, neuron development and brain development, and neuroactive ligand-receptor interaction. Moreover, the qRT-PCR analysis revealed that CD44 was dramatically increased in mice with sleep deprivation induction. The overexpression of CD44 in astrocytes promoted BBB permeability in vitro and induced the expression of downstream gene NANOG. Our results indicate that sleep deprivation upregulated CD44 expression in hippocampus tissue, and increased BBB permeability, resulting in cognitive impairment.